2004
DOI: 10.1128/jvi.78.16.8486-8495.2004
|View full text |Cite
|
Sign up to set email alerts
|

Basic Residues of the Retroviral Nucleocapsid Play Different Roles in Gag-Gag and Gag-Ψ RNA Interactions

Abstract: The Orthoretrovirus Gag interaction (I) domain maps to the nucleocapsid (NC) domain in the Gag polyprotein. We used the yeast two-hybrid system to analyze the role of Alpharetrovirus NC in Gag-Gag interactions and also examined the efficiency of viral assembly and release in vivo. We could delete either or both of the two Cys-His (CH) boxes without abrogating Gag-Gag interactions. We found that as few as eight clustered basic residues, attached to the C terminus of the spacer peptide separating the capsid (CA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 45 publications
0
33
1
Order By: Relevance
“…Mutations in the polybasic region of NC or the zinc fingers impair and even abrogate genomic RNA packaging with the notion that the ZnF and hydrophobic plateau are driving the specificity of gRNA encapsidation, while the basic residues are more involved in Gag-Gag multimerization and assembly. 19,[75][76][77][78] These NC motifs are involved in specific GaggRNA interactions via the Psi signal located in the 5' leader region of the gRNA (Fig. 3).…”
Section: -89mentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in the polybasic region of NC or the zinc fingers impair and even abrogate genomic RNA packaging with the notion that the ZnF and hydrophobic plateau are driving the specificity of gRNA encapsidation, while the basic residues are more involved in Gag-Gag multimerization and assembly. 19,[75][76][77][78] These NC motifs are involved in specific GaggRNA interactions via the Psi signal located in the 5' leader region of the gRNA (Fig. 3).…”
Section: -89mentioning
confidence: 99%
“…Indeed, NC mutants of these motifs are viruses defective in the efficacy of Gag assembly, budding and particle morphogenesis for many retroviruses (HIV, SIV, MLV, RSV, BLV, MPMV). 19,[74][75][76][77][78][81][82][83]85 However, in most cases, some mutant Gag are still targeted to the assembly sites, i.e., at the plasma membrane, but Gag oligomer formation or viral particle budding is, at least in part, prevented and aberrant budding particles are observed in many instances. 76,[82][83][84] In the case of HIV-1, the situation is rather complex due to the fact that NC is located between sp1 and sp2 with the p6 domain at the extreme C-terminus (Fig.…”
Section: -89mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are also consistent with mutagenesis studies showing that Arg61 is important for the high affinity Gag-Ψ RNA binding in vitro and efficient genome packaging in vivo. 40,44,45 The nucleobase of A168 packs against the side chains of Leu49, Cys60 and Lys58, and appears to be stabilized by a hydrogen bond between the A168 phosphate oxygen and Lys58 side chain amino group, Figure 8.…”
Section: Structure Of the Nc:μψ Complexmentioning
confidence: 99%
“…Mutation of the functional domains of NC has shown that the ZFs and basic residues of the HIV and MLV GagNC are involved in gRNA selection and dimerization through tight interactions with the Psi packaging signal. 12,[31][32][33][34][35][36][37][38] Strikingly, loosening the interactions between GagNC and the gRNA by mutating either the NC ZFs or its 5' basic residues, not only reduces the gRNA content of mutant virus but turns HIV-1 into a DNA-containing virus. [38][39][40] These mutant HIVs activate viral DNA synthesis by the viral reverse transcriptase (called "late RT") in HIV-1 producer cells before virus release leading to the packaging of viral DNA (up to 100-fold increase of DNA level as compared with wild-type virions).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%